2012
DOI: 10.5194/bg-9-1173-2012
|View full text |Cite
|
Sign up to set email alerts
|

The moisture response of soil heterotrophic respiration: interaction with soil properties

Abstract: Abstract. Soil moisture is of primary importance for predicting the evolution of soil carbon stocks and fluxes, both because it strongly controls organic matter decomposition and because it is predicted to change at global scales in the following decades. However, the soil functions used to model the heterotrophic respiration response to moisture have limited empirical support and introduce an uncertainty of at least 4% in global soil carbon stock predictions by 2100. The necessity of improving the rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
217
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(240 citation statements)
references
References 42 publications
19
217
3
1
Order By: Relevance
“…rhizosphere priming effect) and soil CO 2 efflux. Many lab incubation studies have shown that soil moisture dynamics can significantly affect CO 2 efflux from root-free soils (Borken and Matzner, 2009;Moyano et al, 2012). This study and two recent studies (Niklaus and Falloon, 2006;Dijkstra and Cheng, 2007b) provide further evidence that soil moisture content and dynamics exert significant control of rhizosphere priming effect and thus CO 2 efflux from soils under the presence of plants.…”
Section: Implications For the Responses Of Soil Co 2 Efflux To Moistusupporting
confidence: 50%
“…rhizosphere priming effect) and soil CO 2 efflux. Many lab incubation studies have shown that soil moisture dynamics can significantly affect CO 2 efflux from root-free soils (Borken and Matzner, 2009;Moyano et al, 2012). This study and two recent studies (Niklaus and Falloon, 2006;Dijkstra and Cheng, 2007b) provide further evidence that soil moisture content and dynamics exert significant control of rhizosphere priming effect and thus CO 2 efflux from soils under the presence of plants.…”
Section: Implications For the Responses Of Soil Co 2 Efflux To Moistusupporting
confidence: 50%
“…The parameters f moist, z and f temp, z are functions depending respectively on soil moisture and soil temperature at a given depth z and affecting the decomposition rate of HSOC. They correspond to the moisture equation from Moyano et al (2012) and to Eq. (3), respectively.…”
Section: General Description Of the Carbosaf Model 251 Organic Carbmentioning
confidence: 99%
“…Then, they normalized such linear models between 0 and 1 to apply these functions to classical first-order kinetics. All details are described in Moyano et al (2012). To save computing time, we calculated f moist, z only once using measured SOC stocks instead of using modeled SOC stocks and repeated the calculation at each time step.…”
Section: General Description Of the Carbosaf Model 251 Organic Carbmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil matric potentials vary over short scales due to the varying size of pores, with microbes concentrated at the interfaces between air and water. Decomposition rates of SOM may therefore be influenced by moisture content (Moyano et al, 2012), pore size and location within an aggregate (Killham et al, 1993) and also by temperature and substrate quality (Davidson and Janssens, 2006) and microbial properties (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%